PERAN PENDIDIKAN ISLAM DALAM MENUMBUHKAN SIKAP TOLERANSI TERHADAP KEBERAGAMAN BUDAYA DI SEKOLAH DASAR - Hsb, Sri Handayani; Fata, Nahriyah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to examine the implementation of multicultural education in forming tolerance attitudes in the elementary school environment. Multicultural education is an important approach in dealing with the cultural, religious, and ethnic diversity that exists in Indonesia, especially in schools with heterogeneous student backgrounds. The research method used was qualitative descriptive with data collection techniques through observation, in-depth interviews, and documentation in several public elementary schools 121 Hutabargot Julu. The results of the study show that the integration of multicultural values in learning and school activities plays a significant role in fostering mutual respect and respect for differences among students. In addition, the role of teachers as facilitators of tolerance greatly determines the success of the implementation of multicultural education. The obstacles found include a lack of training for teachers and not optimal curriculum support. Therefore, education policies that are more responsive to diversity and strengthen teachers' capacity in implementing a multicultural approach in a sustainable manner are needed.